Optical properties of InI3: Density functional theory calculations and experimental results. (15th December 2022) - Sharma, Ashish Kumar; Kumar, Pradeep; Kumar, Arvind; Jungbog, Kim; Vedeshwar, Agnikumar G.
Abstract: The electronic and optical properties of InI3 have been investigated by both experimental and theoretical approaches. The First Principle electronic structure and optical properties were calculated by Density Functional Theory (DFT) formalism using Full Potential Linearized Augmented Plane Wave plus local orbitals (FP-LAPW + lo) implementing different appropriate exchange-correlation functionals in WIEN2k code. The calculations were also carried out implementing other functionals and only TB-mBJ results tally the closest with experimental results. The optical measurements of a well characterized InI3 films indicate the band gap as of direct type and residual strain dependant. The stress free intrinsic band gap E g  = 2.8 eV (average of E g ⊥c and E g IIc ) has been determined from the residual strain dependence of the band gap in closest agreement with theoretically calculated value of 2.9 eV. Both theory and experiment show that the band gap is anisotropic along and perpendicular to c-axis. The electron effective mass m e * = 0.79 m 0 and the hole effective mass m h * = 0.85 m 0 have been determined from the band structure. The experimental and theoretical optical properties match reasonably well. Highlights: Study of physical properties of InI3 is reported for the first time in literature. Optical properties studied by both experiment and density functional theory. Film thickness dependent band gap correlates well with film residual strain. Electron and hole effective masses are determined from the band structure. Experimental and theoretical results match reasonably well.